Persian clitics: Doubling and agreement - Rasekh, Mohammad (Journal of Modern Languages, 2017)
In this paper, different functions of Persian pronominal enclitics in verbal domain are discussed. Traditionally, it has been supposed that these enclitics act as arguments, while it is argued here that they act as agreement markers as well. As they have moved from Wackernagel’s position toward verb adjacent position in different stages of Persian language history, their functions have also changed. Through grammaticalization, they have acquired a new role as subject agreement markers. They may also act as objects in clitic doubling structures, when the optional NP object acts as topic. The new role of these clitics is explained by the blocking principle, which shows how a language acquires new verbal agreement formatives only for the non-distinctive slots of the agreement paradigm.